(untitled) (Scientific journal of the Fergana State University, 2023)
Registered 5 species of the genus Agrotis in South Fergana. According to seasonal aspects, 5 species belong to the spring-summer-autumn ecological group, 1 species to the spring-summer, 2 species to the summer-autumn group. All species of this genus are polyphages, such species as Agrotis segetum, Agrotis exclamationis, Agrotis ipsilon, Agrotis bigramma, Agrotis lasserrei, Agrotis clavis are broad polyphages in terms of nutrition. Agrotis obesa and Agrotis vestigialis are narrow polyphages.